Ruang Gender Haruskah Selalu dipisah? Ruang Kelola Wilayah Adat dan Pendekatan Ekologi Politik Feminis - Betty Tiominar; Suraya A Afiff (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2021)
Gender space generally separates space and place of land and natural resources management and utilization based on gender. The assumption these gender space segregation with firm boundary lines implicated demand to showing women's control, utilization, and management of the land and natural resources on the participatory mapping result that is mostly facilitated by JKPP in Indonesia. One of the purposes of this demand is to include women's interests over space in every decision-making process that has an impact on the women's production areas. In fact, not all places have separated the control, utilization, and management of the land and natural resources based on gender. In an agrarian society, like in Indonesia, most of the areas for control, utilization, and management of the land and natural resources are communal based, which is means that the land and natural resources are joint management by men and women. In one indigenous territory, at two different places and times, gender based management can undergo changes. Taking the case of the Balai Juhu in Hulu Sungai Tengah Regency, South Kalimantan, using a feminist political ecology framework, this article examines the complexities of gender segregation on indigenous territory